Female labor force participation, labor market dynamic, and growth - Monserrat Bustelo; Luca Flabbi; Claudia Piras; Mauricio Tejada (Inter-American Development Bank (IDB), 2019)
The labor force participation of women is lower than the labor force participation of men. This empirical regularity is particularly acute in Latin America and the Caribbean (LAC). In terms of labor market productivity and growth potential, these lower participation rates constitute a reserve of untapped resources. Providing an estimate of the impact that increased female participation in the labor force has on labor market outcomes and GDP is therefore crucial but challenging. Two issues are of importance: sample selection and equilibrium effects. We develop a labor market model that is able to address these issues. We estimate the model on the microdata of five LAC countries. We find that both a childcare policy and a policy increasing women's productivity generate a positive impact on female participation and significant increases in GDP per capita. Our results suggest that relatively modest policies that are able to increase the participation of women in the labor market can provide a significant increase in GDP. However, we are not able to take into account the fiscal costs necessary to implement the policies or the possible negative externalities on household production.
Keywords: J24; J3; J64; O17; 330; Female labor force participation; Labor market frictions; Search and matching; Nash bargaining; Informality